2022
DOI: 10.1136/bcr-2021-245749
|View full text |Cite
|
Sign up to set email alerts
|

Recrudescence of severe polyneuropathy after receiving Pfizer-BioNTech COVID-19 vaccine in a patient with a history of eosinophilic granulomatosis with polyangiitis

Abstract: A middle age man with a history of diabetes mellitus type 2, hypertension, migraine and eosinophilic granulomatosis with polyangiitis (EGPA) with polyneuropathy in remission presented with paresthesia and motor weakness soon after receiving the Pfizer-BioNTech COVID-19 messanger RNA (mRNA) vaccine. The patient had polyneuropathy 10 years ago secondary to EGPA, which had resolved. EGPA was diagnosed on the basis of typical symptoms and positive sural nerve biopsy. Five days after receiving the first dose of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… 3 4 5 Recently, it has been reported that eosinophilic granulomatosis with polyangiitis (EGPA) was diagnosed after the second dose of COVID-19 vaccination, and early diagnosis on patients with EGPA had a recurrence of severe polyneuropathy after vaccination. 6 7 Here, we report the first case of de novo EGPA after COVID-19 vaccination in Korea.…”
Section: Introductionmentioning
confidence: 87%
“… 3 4 5 Recently, it has been reported that eosinophilic granulomatosis with polyangiitis (EGPA) was diagnosed after the second dose of COVID-19 vaccination, and early diagnosis on patients with EGPA had a recurrence of severe polyneuropathy after vaccination. 6 7 Here, we report the first case of de novo EGPA after COVID-19 vaccination in Korea.…”
Section: Introductionmentioning
confidence: 87%